Microgreens are new generation smart food - Koley, Tanmay Kumar; Singh, Sudhir; Prasad, R. N.; Singh, B. (Indian Horticulture, 2019)
Microgreens are a tiny form of young edible greens produced from various kinds of vegetables, herbs and plants. They are harvested at seedling stages which punch in flavour and nutrition. Vitamins, minerals and other bioactive compounds content in microgreens prepared from vegetables are higher and more bioavailable than mature vegetables. Since these tiny plants do not require much specific weather condition, taste, flavour and colour of vegetable, they can be accessed throughout the year.